Biodiversity with problem-based learning: impact on quality of students’ scientific argumentation - Yenny Anwar; Rita Rahmayanti; Ermayanti (Biosfer: Jurnal Pendidikan Biologi, 2021)
This study aims to determine the effect of problem-based learning (PBL) on the scientific argumentation of class X students at Senior High School in Indralaya, Indonesia, on biodiversity education. The research method was quasi-experimental with a non-equivalent control group research design. This research was conducted in class X-science-3 (n=33) as an experiment and X-science 4 (n=33) as a control at Senior High School in Indralaya, Indonesia. The data collection instrument was a test question that included scientific argumentation skills in essay questions and recorded class discussions. Data on writing scientific arguments are analyzed using cohesion and coherence, sentence effectiveness, concept correctness, critical analysis of problems and problem-solving. Data on the ability of scientific argumentation in writing and oral are also analyzed based on Toulmin's claim, data, warrant, backing, rebuttal, and qualifier. Furthermore, based on the Toulmin aspect, the students' quality level of scientific argumentation is determined. The result showed that the level of argumentation quality of students who applied the PBL model was mainly at level 3, while the control class was mainly at level 1. The effect being studied is significant. The PBL can significantly influence the ability of scientific argumentation in class X students at senior high school in Indralaya, Indonesia.